2010
DOI: 10.1002/yea.1802
|View full text |Cite
|
Sign up to set email alerts
|

A novel Hansenula polymorpha transcriptional factor HpHAP4‐B, able to functionally replace the S. cerevisiae HAP4 gene, contains an additional bZip motif

Abstract: The transcriptional regulator HAP4, whose expression is induced on respiratory substrates, has been shown to be involved in the balance between fermentation and respiration in Saccharomyces cerevisiae. We have previously identified a HAP4 orthologue in the yeast Hansenula polymorpha, called HpHAP4-A, which, despite its very limited sequence conservation (a 16 amino acid N-terminal motif), is fully functional in S. cerevisiae. Based on the same N-terminal motif, a second gene has now been identified in the same… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 45 publications
3
17
1
Order By: Relevance
“…9). The iron-dependent regulation of CAP2 expression was first noted in a C. albicans microarray study (14), and indeed for CAP2 orthologs in other systems as well (17,21,79). In iron-replete media, although the CAP2 mRNA level was diminished to a low basal level, the Cap2 protein level was reduced to an undetectable level (Fig.…”
Section: Transcriptional Regulation Of Cap2 Expressionsupporting
confidence: 52%
See 4 more Smart Citations
“…9). The iron-dependent regulation of CAP2 expression was first noted in a C. albicans microarray study (14), and indeed for CAP2 orthologs in other systems as well (17,21,79). In iron-replete media, although the CAP2 mRNA level was diminished to a low basal level, the Cap2 protein level was reduced to an undetectable level (Fig.…”
Section: Transcriptional Regulation Of Cap2 Expressionsupporting
confidence: 52%
“…Complex-There are previous reports that Cap2 or its orthologs likely function in a complex with Hap2-Hap3-Hap5 (19,21,29). In a previous study, three HAP4-like genes and two HAP3-like genes were identified in the C. albicans genome (27).…”
Section: Cap2-dependent Up-regulation Of Components Of the Hap Regulamentioning
confidence: 96%
See 3 more Smart Citations